Akulah Kebangkitan dan Hidup”: Kajian Perikop Yohanes 11:25-26 Dalam Perspektif Teologi Biblis dan Tradisi Gereja - Filbert Ngafrehen (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2026)
The statement of Jesus, “I am the resurrection and the life; he who believes in me will live, even though he dies” (John 11:25-26), is a central Christological text that reveals the nature of Christ as the source of eternal life and the conqueror of death. The purpose of this article is to interpret this text in depth, taking into account the pericope’s structure, narrative context, linguistic analysis, and its theological meaning within the Patristic tradition. The method used is a biblical hermeneutic approach, encompassing literary and narrative analysis to trace the pericope’s position in the Lazarus narrative, linguistic analysis of key Greek words, e.g., Egō eimi, anastasis, zōē, and a theological-patristic analysis linking the biblical reading with the interpretations of the Church Fathers. The study’s results show that through the theophanic formula Egō eimi (I am), Jesus declares his divine identity as the source of life itself (autozōē). This text shifts the paradigm from Jewish futuristic eschatology toward realized eschatology, where resurrection and eternal life have already begun and are realized in fellowship with Christ through faith starting now. Dogmatically, this strengthens the Church’s high Christology, and pastorally, it assures that biological death cannot separate the believer from eternal life.